Template-free and low temperature CVD synthesis of vertically aligned 1-D ZnO nanostructures for photovoltaic devices by precursor oxidation protection. Issue 1785 (2015) - Lim, Taehoon; Martinez-Morales, Alfredo A.
ABSTRACT: Zinc oxide (ZnO) is a crystalline material with diverse morphology, large bandgap and high visible light transparency. All of these characteristics make ZnO a suitable material for applications in optical devices such as photovoltaic cells and photodiodes. Regarding photovoltaic applications, it is necessary to grow ZnO on a transparent conducting oxide (TCO) substrate. In this work, vertically aligned 1-dimensional ZnO have been synthesized on a TCO substrate through chemical vapor deposition (CVD). Although ZnO is capable of being synthesized at lower temperatures through the use of Zn powder precursor, oxidation of precursor remains a significant limiting factor to control dimensional characteristics of the synthesized product. In our work we have developed a method by which ZnO is synthesized under lower temperatures through the prevention of precursor oxidation and control of Zn vapor fluid dynamics. Partial pressure of Zn vapor—a significant factor in the morphology and quality of product—is controlled and maintained during growth. The morphology and crystal structure of the synthesized ZnO is characterized by scanning electron microscopy (SEM) and x-ray diffraction (XRD). We also demonstrate the fabrication of dye-sensitized solar cell (DSSC) with synthesized 1-dimensional ZnO, as a photoelectrode, and compare the photovoltaic characteristics of two devices fabricated under same conditions, except for the photoelectrode utilized.